Creating a Physician-Led Quality Imperative. (November 2014) - Nelson, Marcia F.; Merriman, Charles S.; Magnusson, Peter T.; Thomassian, Kristapor V.; Strawn, Alivia; Martin, Julie
To emerge from a significant quality crisis, hospital administration recognized the need for physician leadership to drive improvements. A framework is presented for a physician-led Quality Summit to select best practice initiatives for implementation over 1 year. Results demonstrated statistically significant reductions in ventilator-associated pneumonia, decreasing from the first quarter 2009 baseline of 8.34 per 1000 ventilator days to 3.32 per 1000 ventilator days in second quarter 2010 ( P = .0055). During the same time frame, catheter-associated urinary tract infections decreased from 4.35 per 1000 catheter days to 0.98 per 1000 catheter days ( P = .0438), and severe sepsis/septic shock mortality declined from 33% to 13% ( P = .0084). The customized World Health Organization Surgical Safety Checklist was used in 93% of surgeries within 1 month of adoption. Venous thromboembolism screening for adults became routine. The annual Quality Summit cycle engages physicians to introduce and spread quality improvement.